Investigações em torno do antropocentrismo e da atual crise ecológica - Choueri Junior, Nelson (2010)
Many environmental ethics thinkers bear the existing ecological crisis is resultig from the fact that both, our thoughts and our actions would be antropocentric. It means that they (our thoughts and our actions) would have the human needs and wishes satisfaction as their only goals. However, a careful investigation about the relationship among humans could perhaps unveil that we are not antropocentric yet. The aim of this work is to enlighten this: whether we think and act in an antropocentric way as it seems to be largely accepted. It seems that we have found a satisfatory answer to the question